The effect of 10 at.% Al addition on the hydrogen storage properties of the Ti0.33V0.33Nb0.33 multi-principal element alloy. (July 2022) - Pineda-Romero, Nayely; Witman, Matthew; Stavila, Vitalie; Zlotea, Claudia
Abstract: We report here a thorough study on the effect of 10 at.% Al addition into the ternary equimolar Ti0.33 V0.33 Nb0.33 alloy on the hydrogen storage properties. Despite a decrease of the storage capacity by 20%, several other properties are enhanced by the presence of Al. The hydride formation is destabilized in the quaternary alloy as compared to the pristine ternary composition, as also confirmed by machine learning approach. The hydrogen desorption occurs at lower temperature in the Al-containing alloy relative to the initial material. Moreover, the Al presence improves the stability during hydrogen absorption/desorption cycling without significant loss of the capacity and phase segregation. This study proves that Al addition into multi-principal element alloys is a promising strategy for the design of novel materials for hydrogen storage. Highlights: A novel single-phase bcc multi-principal alloy Al0.10 Ti0.30 V0.30 Nb0.30 was prepared. It absorbs hydrogen quickly at room temperature forming a fcc di-hydride (1.6H/M). Fcc hydride formation is destabilized as compared to equimolar TiVNb composition. The capacity is stable during hydrogen absorption/desorption cycling.